2016
DOI: 10.1007/s00436-016-5307-8
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Baylisascaris spp. in captive striped skunks (Mephitis mephitis) in some European areas

Abstract: Skunks are popular carnivore species kept both in zoological institutions and in households where they are hand raised as exotic pets. These small carnivores are considered the main definitive hosts of the roundworm Baylisascaris columnaris. The purpose of this survey was to investigate the occurrence of Baylisascaris spp. in striped skunks kept as pets or in private zoo collections in some European areas. Copromicroscopic data from two laboratories, one in Italy and one in Germany, were used. A total of 60 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…resulted in partial sequences for B. columnaris Cox1 (413 bp) and Cox2 (483 bp) genes (Franssen et al., 2013). The availability of these sequences has facilitated the molecular identification of these parasites for us as well as other researchers (d'Ovidio et al., 2017). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…resulted in partial sequences for B. columnaris Cox1 (413 bp) and Cox2 (483 bp) genes (Franssen et al., 2013). The availability of these sequences has facilitated the molecular identification of these parasites for us as well as other researchers (d'Ovidio et al., 2017). …”
Section: Discussionmentioning
confidence: 99%
“…A recent study on the prevalence of B. columnaris in captive European skunks found that ∼25% of skunks tested were infected with B. columnaris (d'Ovidio et al., 2017). Data indicates that in our study area there is a much higher infection rate of Striped skunks than reported in studies of captive Striped skunks in Europe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Worm burdens were not determined, but in one study, eggs per gram of feces (EPG) ranged from 150 to 14,500 (mean of 4713 EPG) (d'Ovidio et al., 2016). This is relatively low compared to natural B. procyonis infections, which may average 26,000 EPG (Kazacos, 2016).…”
Section: New World Species Of Baylisascarismentioning
confidence: 99%
“…Contemporary surveys on B. columnaris are generally lacking; more surveillance is needed to accurately characterize the distribution and eco-epidemiology of this parasite because most recent reports are from captive pet skunks ( d’Ovidio et al., 2016 ). From published reports, B. columnaris appears to be well-established in the northeast, upper Midwest, and prairie regions of the United States and Canada, apparently uncommon in arid regions of the west and southwest ( Table 2 ).…”
Section: New World Species Of Baylisascarismentioning
confidence: 99%